DAMPAK PENERAPAN PP NOMOR 46 TAHUN 2013 ATAS PEMBAYARAN PAJAK OLEH WAJIB PAJAK KPP PRATAMA MANADO - Rawun, Yuli; Poputra, Agus T.; Kalangi, Lintje (Universitas Sam Ratulangi, 2015)
In an effort to increase voluntary compliance with tax obligations and encourage the contribution of revenues from the UMKM sector, the Government has issued Government Regulation No. 46 2013. The new Tax Regulation has the advantage of rates that are used less than the previous fare, ie 1% of gross turnover.Regulation No. 46 2013 taxpayer applies for personal and / or agency that has a certain gross income, ie income less than 4.8 M. The aim of this study was to analyze the impact of adoption of Government Regulation No. 46 2013 of Paying Income Tax by Taxpayers at KPP Pratama Manado. The analytical method used is using two different test samples / dependent groups (paired) or Paired Sample T Test. Paired Sample t test course used when the two groups are interconnected. Two paired sample means a sample with the same subject but have two different treatments or measurements of, for example, before and after. Results of this study indicate that there is a difference between before and after the enactment of Government Regulation No. 46 Year 2013, but the difference that causes a decrease in the amount of tax paid by individual taxpayers who use the recording but for individual taxpayers who use the books there is no significant difference. As for corporate taxpayers that difference causes an increase on the amount of income tax payments by using final tax. Thus the application of Regulation No. 46 Year 2013 needs to be socialized again to taxpayers who are not registered in the KPP Pratama Manado in order to increase the amount of income tax payments.